Multi-carrier switching strategy for high-bandwidth potential balancing control of multilevel inverters - Zuraidi Md Tahir; Auzani Jidin; Mohd Luqman Mohd Jamil (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This paper confers on investigation of a direct torque control (DTC) of induction motor drive by 3 level neutral point clamp (NPC) multilevel inverter. The imbalance problem may deteriorate the electric drive performances which might cause a short circuit condition. Various balancing control strategies were proposed, however, most of them employed complex space vector modulation (SVM) and hysteresis-based controller that generates variable switching frequencies. The proposed method will offer a reliable balancing control strategy with a constant switching frequency, and moreover, it will provide excellent electric drive performances. This research proposed a new multi carrier switching modulation strategy that establish a high-band-width control for neutral point potential in the NPC inverter. Potency of the proposed high-bandwidth potential balancing strategy is validated through the MATLAB/SIMULINK environment.